UPAYA AMERIKA SERIKAT UNTUK MEREDAM POTENSI KONFLIK TERBUKA ANTARA JEPANG DENGAN CINA DALAM KASUS SENGKETA KEPULAUAN SENKAKU - Muthia Dwi Damayanti (HI 15 UMY 005, 2015)
*5 Under the administration of President Obama, U.S’s foreign policy is promoting Pivot to Asia. Pivot to Asia itself shows U.S’s concern toward Asian Countries. One of U.S Pivot to Asia’s action can be seen in United States’s effort to reduce potential conflict between Japan and China in senkaku islands. The reason behind U.S’s involvement can be explained through system theory. If this theory applied in this case, U.S’s effort to reduce potential conflict is because U.S has interdependency relation with China and Japan, particularly in terms of economy. The aim of this article is to find out what is the reason behind U.S’s position to choose peace resolution in Senkaku dispute.